Monumental buildings in the revitalization process of historic urban quarters: The case of the walled city of famagusta - Doratli, Naciye (Taylor and Francis, 2016)
Following this changing attitude, a number of international agreements for the protection of these values have been signed and implemented. Within the Council of Europe, the European Charter of the Architectural Heritage (1975) introduced the term ‘integrated conservation’, and the Granada Convention for the Protection of the Architectural Heritage of Europe (1985) laid further stress on this aspect and added as its major contribution a definition of the different forms of architectural heritage. ‘Integrated conservation’ comprises the requirement to include conservation as a necessary part of spatial and urban planning, establishing links between heritage protection and cultural activities, and preserving technical and traditional skills. It places emphasis on the importance of conservation through revitalization and indicates indirectly the necessity of strategic approaches towards conservation through a process of revitalization. © 2012 Michael J. K. Walsh, Peter W. Edbury, Nicholas S. H. Coureas and the Contributors.